Late lunch with llamas eaudiobook - Osborne, Mary Pope (Magic Tree House, 2020)
The #1 bestselling Magic Tree House series is ready to whisk you away through time with Jack and Annie—this time to South America! When the magic tree house whisks Jack and Annie to a mountainside, they are surprised to find farmers nearby. Then they learn that the farmer's baby llama has been stolen, and Jack and Annie vow to bring the little animal back to its owners. But the journey is treacherous—they must climb to the peak of Machu Picchu and climb back down in order to complete this mission. Jack and Annie have been on many dangerous travels, but can they survive this one? Track the facts with Jack and Annie in the nonfiction companion to this book: Llamas and the Andes . Did you know that there's a Magic Tree House book for every kid? Magic Tree House: Perfect for readers who are just beginning chapter books Merlin Missions: More challenging adventures for the experienced reader Fact Trackers: Nonfiction companions to your favorite Magic Tree House adventures If you're looking for Merlin Mission #34: Season of the Sandstorms , it was renumbered as part of the rebrand in 2017 as Merlin Mission #6.